EFFECTING FACTORS OF CUSTOMER SATISFACTION - Özkan, Coşkun; Akman, Gülşen; Özcan, Burcu (International Journal of Industrial Engineering: Theory, Applications and Practice, 2010)
To be successful in global competitive markets, many firms have responded to rapid technological change, heightened competition and shortened product life cycles by focusing customer satisfaction. It is very difficult to ensure customer satisfaction. In spite of the increasing offer, customers are more conscious, and they make purchasing decisions by evaluating multiple choices and selecting among these choices. In this paper, supplier performance was evaluated by their customers and then, effects of performance criteria factors on customer satisfaction were analyzed. To examine the role of supplier performance in customer satisfaction, a survey was conducted of 182 manufacturing companies in Turkey. Factor analysis yielded seven factors: technical capability, innovation, conformance quality, pricing, delivery, flexibility and service. Correlation analysis indicated that innovation, delivery, flexibility and service factors significantly correlated with customer satisfaction. Hierarchical multiple regression analysis suggested that delivery, flexibility, service and innovation significantly contributed to the customer satisfaction.